Outcomes of Shoulder Functions in Spinal Accessory to Suprascapular Nerve Transfer in Brachial Plexus Injury: A Comparison between Anterior and Posterior Approach - Maurya, Sanjay; Renganathan, Gopi; R., Venkatnarayanan; Bharti, Rajiv (Indian Journal of Plastic Surgery, 2021)
Background Restoration of shoulder functions is important in brachial plexus injury (BPI). The functional outcomes of spinal accessory nerve (SAN) to suprascapular nerve (SSN) transfer by the anterior supraclavicular approach and the posterior approach is a matter of debate. This article aims to compare the outcomes of the shoulder functions by the SAN to the SSN transfer using the two approaches.Methods Retrospective data was collected in 34 patients who underwent SAN to SSN transfer from January 2016 to June 2018. Group A included 16 patients who underwent nerve transfers by anterior approach, and Group B included 18 patients who underwent nerve transfers by posterior approach. Functional outcomes were measured by grading the muscle power as per the British Medical Research Council (MRC) grading (graded as M) and the range of motions (ROM) of the shoulder at 6 months and 18 months.Results Early recovery was seen in group B with 7 patients (39%) showing M1 abduction power at 6 months as compared with one patient (6%) in group A . This difference was statistically significant (p value = 0.04). At 18 months, 10 patients (62%) in group A had good recovery (MRC grade ≥3), while 13 patients (72%) in group B had a good recovery. This difference was not found to be statistically significant (Fisher exact test p value = 0.71) There was no statistical difference in the outcomes of ROM in shoulder abduction, external rotation, and motor power at 18 months of follow-up.Conclusions Early recovery was observed in the posterior approach group at 6 months, however, there was no significant difference in the outcomes of shoulder functions in muscle power and ROM in the two groups at 18 months of follow-up.
Keywords: nerve transfer; brachial plexus injury; posterior approach; suprascapular nerve; spinal accessory nerve